Sistema de deteccion de fallas en las pistas de rodamientos, usando el analisis de espectros de frecuencias en señales acusticas - Aguilar Liza, John Williams (2016)
The development of this paper titled "Fault Detection System in the bearing races using the frequency spectrum analysis in acoustic signals", aims to design a mechatronic system which is able to analyze the frequency spectrum; also contrast the results with similar studies by analyzing vibrations in the bearings. For the development of a pilot project it was implemented bank; consisting of a single phase AC motor of 0.5 HP, 2 row deep groove ball bearings, shaft pre HS machining steel, a metal disc and a computer microphone, allowing us to acquire acoustic vibration signals of a bearing process your signal through the program developed in MATLAB-Simulink and get a significant spectrum as a comparison between theory and Vibration analysis of acoustic signals. Since the foundation of the art of acoustic signals, the power to detect defects in the bearings without having direct contact with the bearing housing, thanks to the reception of pressure waves in the membrane of the microphone, which are the same as generated on solid media, however a low pass filter, in order not to allow unwanted signals designed. The result is a comprehensive report of the simulation carried out, together with detailed drawings of equipment and recruitment analysis of frequency spectra.